Formulation and in -vitro evaluation of chrysophanol topical gel - Vasudevan, Deepa T; Gopalakrishnan, S; Dinesh, Kavitha R; Ravikumar, KG; Sundaram, KR; Unni, AKK (Asian Journal of Pharmaceutics (AJP), 2014)
This study describes the formulation and characterization of topical gel of chrysophanol containing carbopol as gel base. The partition of drug between skin and the hydrogel matrix was considered to play an important role in the permeation process. The effect of three levels of carbopol and three different permeation enhancers on chrysophanol permeability was determined in vitro. Each formulation was characterized in terms of viscosity, pH, extrudability, spreadability, homogenicity, drug content, skin irritation, stability, and drug release studies. The gel consisting of 1% carbopol as gel base and 15% dimethylsulfoxide showed superior physicochemical and permeability properties and it was ranked best. Reports of pharmacokinetic parameters showed that the drug release is controlled by both diffusion and relaxation processes.